Analysis of the Paskibraka Acceptance Selection Sensitivity Test Using Topsis and Promethee Methods at the Youth and Sports Office of Bengkulu City - Pardi Hardianto; Asnawati Asnawati; Sapri Sapri (Jurnal Komputer, Informasi dan Teknologi, 2021)
The Youth and Sports Office of Bengkulu City is a selection committee for Paskibraka candidates which is carried out every year. The assessment of post-baraka candidates consists of 8 aspects, namely Parade, PBB, Psychotest, Samapta/Physical, Health and Fitness, Interview, Regional Arts, and General Knowledge (data attached). The results of the assessment will be recapitulated to determine which participants succeeded in passing and which participants failed to pass, so that from this recapitulation it can be announced at the end of the selection activity. The analysis of the sensitivity test for the selection of paskibraka admissions using the TOPSIS method and the Promethee method at the Bengkulu City Youth and Sports Office was carried out by comparing the final results obtained from the two methods based on the assessment data of each paskribraka candidate. The analysis is done by looking at the number of criteria used, the processing time and also the ranking results. In helping the process of comparative analysis of the two methods, an application was built using the Visual Basic .Net programming language. where the application will show the results of the comparison of the TOPSIS and Promethee methods. Based on the tests that have been carried out, the results show that the application functionality can run well and is able to display the results of the assessment on each prospective paskibraka according to the stages of the TOPSIS and Promethee methods, in terms of processing time the TOPSIS method is faster than the Promethee method.